Domestication effect of reduced brain size is reverted when mink become feral - Pohle, Ann-Kathrin; Zalewski, Andrzej; Muturi, Marion; Dullin, Christian; Farková, Lucie; Keicher, Lara; Dechmann, Dina K. N. (Royal Society Open Science, 2023)
A typical consequence of breeding animal species for domestication is a reduction in relative brain size. When domesticated animals escape from captivity and establish feral populations, the larger brain of the wild phenotype is usually not regained. In the American mink (Neovison vison), we found an exception to this rule. We confirmed the previously described reduction in relative braincase size and volume compared to their wild North American ancestors in mink bred for their fur in Poland, in a dataset of 292 skulls. We then also found a significant regrowth of these measures in well-established feral populations in Poland. Closely related, small mustelids are known for seasonal reversible changes in skull and brain size. It seems that these small mustelids are able to regain the brain size, which is adaptive for living in the wild, and flexibly respond to selection accordingly.